Studi Pengaruh Covid-19 Pada Berbagai Sektor Pengguna Tenaga Listrik di Bangka Belitung - Fajar Ramadani; Asmar Asmar; Rika Favoria Gusa; Wahri Sunanda (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2023)
Electricity in Indonesia, especially in the Bangka Belitung Islands, has been affected by the COVID-19 pandemic. The effect occurred at the beginning of the pandemic in the second quarter of 2020, namely the household sector rose to 3.3%, the social sector fell -3.1%, the industrial sector rose to 15%, business fell -9.8%, the office sector government buildings rose 3%, and the public/other street lighting sector fell -47%. By using statistical tests on the classical assumption test all sectors are normally distributed. In the partial test using multiple linear regression test for the household sector, industry, and government office buildings, only connected power affects energy consumption, namely 70.5%, 97.7%, and 37.4%. In the social and business sectors, there is an effect of connected power and tariff prices on energy consumption, namely 92% and -13%, while business is 42% and 10%, respectively. By using the simultaneous test, the household sector has an effect of 68.2%, the social sector is 75.5%, the industrial sector is 97.5%, the business sector is 44.2% and government buildings are 32.5%.